Silken Prey : Lucas Davenport #23 - Sandford, John, 1944 February 23-; Ferrone, Richard; Recorded Books, LLC.; Penguin Audio (Firm) (Prince Frederick, MD : Recorded Books, 2013)
At 1:15 AM, a Minnesota political fixer answers his doorbell. The next thing he knows, he's on the floor of a moving car, lying on a plastic sheet, his body wet with blood. Lucas Davenport is investigating another case when the trail leads to the man's disappearance, then, very troublingly, to the Minneapolis police department itself, and then, most troublingly of all, to a woman who could give Machiavelli lessons.
Compact disc.
Title from container.
Release date supplied by publihser.
Recording originally produced by Penguin Audio, p2013.
In container (17 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Minneapolis -- Fiction; Minneapolis (Minn.) -- Fiction; Mystery fiction; Audiobooks